Front Cover: Mechanistic and Kinetic Investigations of ON/OFF (Photo)Switchable Binding of Carbon Monoxide by Chromium(0), Molybdenum(0) and Tungsten(0) Carbonyl Complexes with a Pyridyl‐Mesoionic Carbene Ligand (Chem. Eur. J. 51/2022). Issue 51 (1st September 2022) - Boden, Pit J.; Di Martino‐Fumo, Patrick; Bens, Tobias; Steiger, Sophie T.; Marhöfer, Daniel; Niedner‐Schatteburg, Gereon; Sarkar, Biprajit
Abstract : Kinetic and mechanistic investigations of the photo‐induced reversible binding and release of CO to Cr 0, Mo 0 and W 0 complexes with pyridyl‐mesoionic carbene ligands ([LM(CO)4 ]) are reported. Irradiation of the complexes in the solid state at 10 K leads to a FTIR spectroscopically detectable intermediate [LM(CO)3 ] without ligand–sphere reorganization. In solution, clean conversion to a stable photoproduct [LM(CO)3 Xaxial ] (X=MeCN, BuCN, Py) is observed. The photodissociation quantum yield increases from W 0 via Mo 0 to Cr 0 up to 46 %. It is remarkable that there is a fully reversible CO exchange, especially as the reverse recombination reaction with the solvated CO can take hours (Cr≪Mo<W); this opens a new field of highly selective (photo)switchable transition metal complexes. More information can be found in the Research Article by G. Niedner‐Schatteburg, B. Sarkar, and co‐workers (DOI: 10.1002/chem.202201038 ).